2019
DOI: 10.5527/wjn.v8.i7.109
|View full text |Cite
|
Sign up to set email alerts
|

Broad spectrum of interferon-related nephropathies-glomerulonephritis, systemic lupus erythematosus-like syndrome and thrombotic microangiopathy: A case report and review of literature

Abstract: BACKGROUNDInterferons (IFNs) are characterized by a wide range of biological effects, which justifies their potential therapeutic use in several pathologies, but also elicit a wide array of adverse effects in almost every organ system. Among them, renal involvement is probably one of the most complex to identify.CASE SUMMARYWe describe four cases of kidney damage caused by different IFN formulations: IFN-β-related thrombotic microangiopathy, IFN-β-induced systemic lupus erythematosus, and two cases of membrano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…However, it has been reported that the decrease of IFN-β expression can indirectly alleviate the damage of TLR3 activator to glomerular endothelial cells ( Hirono et al, 2020 ). In some cases, IFN-β therapy for relapsing-remitting multiple sclerosis (RRMS) has resulted in LN or thrombotic microangiopathy ( Allinovi et al, 2017 ; Gianassi et al, 2019 ). Pegylated -IFN-α 2B treatment of chronic hepatitis C can lead to MN, while no recurrence of kidney disease was observed after stopping the treatment of IFN ( Gianassi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been reported that the decrease of IFN-β expression can indirectly alleviate the damage of TLR3 activator to glomerular endothelial cells ( Hirono et al, 2020 ). In some cases, IFN-β therapy for relapsing-remitting multiple sclerosis (RRMS) has resulted in LN or thrombotic microangiopathy ( Allinovi et al, 2017 ; Gianassi et al, 2019 ). Pegylated -IFN-α 2B treatment of chronic hepatitis C can lead to MN, while no recurrence of kidney disease was observed after stopping the treatment of IFN ( Gianassi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, IFN-β therapy for relapsing-remitting multiple sclerosis (RRMS) has resulted in LN or thrombotic microangiopathy ( Allinovi et al, 2017 ; Gianassi et al, 2019 ). Pegylated -IFN-α 2B treatment of chronic hepatitis C can lead to MN, while no recurrence of kidney disease was observed after stopping the treatment of IFN ( Gianassi et al, 2019 ). However, this MN is not idiopathic, and recombinant IFN-α has been reported to have a therapeutic effect on Hepatitis B associated MN ( Lin, 1995 ; Lopes Neto et al, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…We postulated that these histological findings were compatible with GN, secondary to SARS-CoV-2 itself or to another superimposed infection, yet no other infection was documented in this patient. The possibility that the causative agent was prior treatment with IFN was also initially raised, in which context, this drug has been associated with a broad spectrum of glomerulopathies [ 19 , 20 ]. Nevertheless, the IgA-DIAGN emerged approximately seven weeks after IFN treatment, and the histological findings in this patient are unlikely to be related to interferon.…”
Section: Discussionmentioning
confidence: 99%
“…There is a broad spectrum of interferon-related complications including glomerulonephritis, systemic lupus erythematosus (SLE)-like syndrome, and thrombotic microangiopathy that may be associated with hypocomplementemia. [ 30 31 ] Drug-induced lupus erythematosus is a syndrome with clinical and serological features similar to SLE that is temporally related to continuous drug exposure and resolves after discontinuation of the drug. More than 90 drugs, including interferons, are involved in causing the disease.…”
Section: Discussionmentioning
confidence: 99%